The Effectiveness Of Using The Online Payment Monitoring System (Mpos) On Restaurant Tax Collection In Enrekang District - Fatimah Fatimah; Hernianti Harun (Jurnal Riset Perpajakan: Amnesty, 2022)
This study aims to determine the effectiveness of the use of MPOS on restaurant tax collection in Enrekang Regency and to find out what obstacles are faced by restaurant owners in collecting restaurant taxes using the Monitoring Online Payment System (MPOS). The analytical model used is the analysis of the calculation of potential revenue which is based on the number of restaurant taxpayers, the calculation of the effectiveness of the restaurant tax is based on the realization of revenue and potential revenue of the Restaurant Tax. The obstacles that are often faced by restaurant owners in collecting Restaurant Tax using the MPOS tool are the tax system that is difficult for the public to understand, the tax deposit system that imposes a burden on restaurant owners, and the lack of compliance level of taxpayers or customers. The results of the study are expected to help local governments increase local revenue (PAD), especially local taxes on restaurants in Enrekang Regency. MPOS is a tool that calculates the amount of tax collected every day in a restaurant. The owner of the restaurant is obliged to collect, the taxpayer is the customer who eats at the restaurant. With this tool, there will be honesty from the restaurant owner in its management system